KARAKTERISTIK PENUMPANG PENGGUNA BUS AKDP DI TERMINAL LARANGAN, SIDOARJO - Agustapraja, Hammam Rofiqi; Dhana, Rio Rahma (Politeknik Negeri Semarang, 2023)
Sidoarjo is a city that is also affected by the development of Surabaya, where many Sidoarjo residents have activities and work in Surabaya so that community mobilization from these two cities is very important and needed, one of them is by using public transportation modes of the AKDP Bus (Inter Cities In The Province Bus), Sidoarjo (Larangan Bus Station) - Surabaya (Semut). The purpose of this study is that in the development of public transportation, especially the Sidoarjo-Surabaya AKDP Bus route, at the Larangan Bus Station, it is adjusted to the characteristics of existing passengers, to create a public transportation mode that suits the needs of the community. The method used in this study is by distributing questionnaires to 100 correspondents with an error rate of 10%, from the primary data obtained characteristics of passengers of the Sidoarjo-Surabaya AKDP Bus as follows: The majority of male passengers (67%) with an age range between 41-50 years (33%) with a high school education background (SMA) (36%), and the majority have other jobs (51%) and private employees (29%). While the majority of passengers using AKDP Bus Transportation in the Prohibition Terminal are a majority with the aim of shopping (80%) and the frequency of using AKDP Bus Transportation <5 times a week (93%). The results of this analysis are expected to be a reference for the management in developing the Sidoarjo-Surabaya AKDP Bus service to be even better.